Discovery of vascular endothelial growth factor receptor tyrosine kinase inhibitors by quantitative structure–activity relationships, molecular dynamics simulation and free energy calculation. Issue 42 (11th April 2016) - Wang, Juan; Shu, Mao; Wen, Xiaorong; Wang, Yuanliang; Wang, Yuanqiang; Hu, Yong; Lin, Zhihua
Abstract : Employing the combined strategy to understand the features of KDR–ligands complexes, and provide a basis for rational design of inhibitors. Abstract : Vascular endothelial growth factor (VEGF), along with its receptor tyrosine kinases VEGFR-2 or kinase insert domain receptor (KDR), are targets for development of novel anticancer agents. Accurately predicting the structural characteristics of the target and chemical features of ligands can greatly reduce the cost and shorten the cycle of designing selective KDR inhibitors with desired activity. In this study, a docking strategy and three dimensional holographic vector of atomic interaction field (3D-HoVAIF) were applied in QSAR analysis of KDR inhibitors. The optimal model was constructed by using stepwise regression combined with partial least squares regression (SMR-PLS). Integrating the results of QSAR analysis, ADMET, pharmacophore modeling and a reverse screening strategy, eight derivatives were identified as potential KDR inhibitors. Then molecular dynamics (MD) simulations and free energy calculations were employed to explore the detailed binding process, so as to compare the potential binding modes of inhibitors with different activities. By analyzing the key residues in the binding site, it was found that different KDR–ligand complexes had similar binding modes. The predicted binding affinities were highly correlated with the experimental biological activity. Free energy analysis indicated that van der Waals interactions provided the major driving force for the binding process. Furthermore, key residues, such as Leu840, Val848, Ala866, Lys868, Leu889, Val899, Thr916, Phe918, Cys919, Leu1035, Cys1045, Asp1046, and Phe1047 played a vital role in forming hydrogen bonds, salt bridges, and hydrophobic interactions with the conformation of KDR. The above results will help design more efficient KDR inhibitors.